IDENTIFIKASI BAKTERI PADA IKAN MAS (Cyprinus carpio) DI PASAR TRADISIONAL LAMBARO, ACEH BESAR - Mutia, Cut; AS, Agus Putra; Febri, Suri Purnama (JURNAL PERIKANAN TROPIS, 2024)
AbstractGoldfish (Cyprinus carpio) is a quite developed freshwater fish for consumption in Indonesia, and hence, demand for goldfish products is high enough. The significant increase in production is caused by the breeding activities. Bacteria attack is one of the factors affecting the amount of production from fish sales, which results in the amount of fish production decreasing drastically due to disruption of growth or mass deaths. Therefore, the aim of this research is to identify what type of bacteria infecting goldfish (Cyprinus carpio) in the Lambaro traditional market, Aceh Besar through biochemical tests. Carried out from December 18th 2023 to January 9th 2024, the samples were taken from 3 sellers, with 5 individuals per seller. Bacterial identification was executed at the Fish Quarantine Station Laboratory, Quality Control and Safety of Aceh Besar Fishery Products. The results of biochemical tests found 4 genera of bacteria that infect goldfish, namely Aeromonas sp., Escherichia coli., Salmonella sp, and Shigella sp. The most common type of bacteria found was Aeromonas sp, which was found in 41 goldfish samples. Key words: Goldfish, identification, biochemical test